LINGUISTIC CHARACTERISTICS OF GENDER AFFILIATION (Conferencea, 2022)
In this thesis, the concept of “linguistic features of gender affiliation” is first explored as an object of linguistics in a communicative environment. The importance of gender affiliation in choosing a social role in society is highlighted.